If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-4 + 7x) = 34 (-4 * 2 + 7x * 2) = 34 (-8 + 14x) = 34 Solving -8 + 14x = 34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 14x = 34 + 8 Combine like terms: -8 + 8 = 0 0 + 14x = 34 + 8 14x = 34 + 8 Combine like terms: 34 + 8 = 42 14x = 42 Divide each side by '14'. x = 3 Simplifying x = 3
| .75t+.125=.75t*6 | | -4x-6=-16-6x | | 2(5y-1)+y=4(y-5)-3 | | x^4=9.14 | | 5(4x-4)=10x-10 | | 2(4a-12)+39=6a+1 | | 2(1-4x)=-54 | | xr^2=s | | d=85 | | 4/3x-5=-3 | | 7n^2+6n-17=0 | | 3x+6=12-x | | (4x+9)+(8x+53)=180 | | (2x^2y-3y^2)dx+(3x^2-2xy)dy=0 | | 11(6x+11)=x | | b-25=25 | | 4r^2+18r=-17 | | (2x^2y-3y^2)+(3x^2-2xy)=0 | | rx^2=s | | 4(12-x)=6(x+7) | | 3(2w-3)+17+w=9w-2(w-8) | | 4x+7-x=47 | | 2x-2=-3x-27 | | 12-9h=-78 | | x+30=4x+3 | | -x+6=4x | | 27-(4t-9)=7(3+9t) | | (-4-4i).(2-3i)=0 | | 5n+36=2(7n-9) | | (3x-6)=5 | | (2)*(2x+7)=(16)*(x-1) | | -18+4y+32=-6x |